Exploring malaria prediction models in Togo: a time series forecasting by health district and target group - Muriel Rabilloud; Nicolas Voirin; Anne Thomas; Tchaa Abalo Bakai; Tinah Atcha-Oubou; Tchassama Tchadjobo (BMJ Open, 2024)
Objectives Integrating malaria prediction models into malaria control strategies can help to anticipate the response to seasonal epidemics. This study aimed to explore the possibility of using routine malaria data and satellite-derived climate data to forecast malaria cases in Togo.Methods Generalised additive (mixed) models were developed to forecast the monthly number of malaria cases in 40 health districts and three target groups. Routinely collected malaria data from 2013 to 2016 and meteorological and vegetation data with a time lag of 1 or 2 months were used for model training, while the year 2017 was used for model testing. Two methods for selecting lagged meteorological and environmental variables were compared: a first method based on statistical approach (‘SA’) and a second method based on biological reasoning (‘BR’). Both methods were applied to obtain a model per target group and health district and a mixed model per target group and health region with the health district as a random effect. The predictive skills of the four models were compared for each health district and target group.Results The most selected predictors in the models per district for the ‘SA’ method were the normalised difference vegetation index, minimum temperature and mean temperature. The ‘SA’ method provided the most accurate models for the training period, except for some health districts in children ≥5 years old and adults and in pregnant women. The most accurate models for the testing period varied by health district and target group, provided either by the ‘SA’ method or the ‘BR’ method. Despite the development of models with four different approaches, the number of malaria cases was inaccurately forecasted.Conclusions These models cannot be used as such in malaria control activities in Togo. The use of finer spatial and temporal scales and non-environmental data could improve malaria prediction.